SENTENCE PROBLEMS IN ARGUMENTATIVE ESSAY FACED BY THE SECOND SEMESTER ENGLISH LANGUAGE EDUCATION STUDENTS - Maria Wulandari; Syafrianto SM; Wizarotul Maghfiroh (JR-ELT (Journal of Research in English Language Teaching), 2026)
This study aims to examine the types of sentence problems commonly found in argumentative essays written by second-semester students in an English Language Education study program. As writing is a fundamental skill in academic communication, identifying sentence-level issues is crucial for improving students’ writing proficiency. This research employs a qualitative descriptive method, with data collected from 30 students' final argumentative essay assignments. The analysis draws on the sentence problem framework, including sentence fragments, comma splices, run-on sentences, choppy sentences, and stringy sentences. To analyze the data, interactive model consisting of data condensation, data display, and conclusion drawing was utilized. The findings show that there are 47 data of sentence problems such as fragments (49%), comma splices (30%), stringy sentences (11%), run-on sentences (9%), and choppy sentences (2%). These recurring problems highlight the need for more focused instruction on sentence-level writing. The study concludes by recommending specific pedagogical interventions aimed at enhancing students’ grammatical awareness and sentence structuring skills to support the development of clearer and more effective academic writing.